Analytical model and design approach for FRP strengthening of non-conforming RC corner beam–column joints. (15th March 2015) - Del Vecchio, Ciro; Di Ludovico, Marco; Prota, Andrea; Manfredi, Gaetano
Highlights: The mechanical behavior of FRP strengthened beam–column joints is closely examined. A new strength capacity model has been proposed to account for the FRP strengthening. The model is optimized to be a simple and reliable tool suitable for practical applications. The model accounts for different joint dimensions and strengthening layouts. The model has been validated on a large set of experimental data. Abstract: The high vulnerability of existing reinforced concrete (RC) structural systems is often related to brittle failures of critical members. Field surveys and relevant scientific studies showed that unconfined and poorly detailed beam–column joints were not able to resist moderate-to-large seismic events. Several strengthening techniques have been proposed to improve the seismic capacity of existing RC beam–column joints. The effectiveness of composite materials, such as fiber reinforced polymer (FRP) systems, has been demonstrated by experimental tests on joint subassemblies and entire structural systems. This, along with the simplicity of installation, has strongly promoted the use of the composite material for seismic retrofit of RC structures. However, the large number of parameters affecting the mechanical behavior of FRP strengthened beam–column joints makes the development of reliable capacity models complex. In recent years several proposal have been advanced, but a simple and generalized formulation is still lacking. This paper presents a new strength capacity model to account for the strength increase provided by FRP systems in the seismic retrofit of poorly detailed corner joints. A large database of experimental tests has been analyzed to assess the accuracy of the proposed model. The simple theoretical approach and the use of experimentally determined parameters make this model suitable for practical applications.